Analysis of Public Response to the Management of Green Open Space Putri Pinang Masak Park Jambi City: Analisis Respon Masyarakat Terhadap Pengelolaan Ruang Terbuka Hijau Putri Pinang Masak Park Kota Jambi - Mutiara Salsilina; Michael Lega; Suci Rahmadani (Universitas Indo Global Mandiri, 2026)
Purpose: This study aims to analyze public responses to the management of green open space at Putri Pinang Masak Park Jambi City and to identify the factors influencing public access and utilization of the green open space. Methodology: This study employed a qualitative approach with a descriptive method. Data were collected through in-depth field observations and semi-structured interviews with visitors of Putri Pinang Masak Park, selected using a purposive sampling technique. The data were analyzed inductively through data reduction, data display, and conclusion drawing, validated via source triangulation. Findings: The results indicate that public responses to the management of GOS at Putri Pinang Masak Park reveal a gap between physical infrastructure development and operational sustainability. Although the available facilities are relatively complete, management tends to be reactive, leading to a decline in vegetation quality and environmental comfort. Furthermore, non-physical accessibility barriers were identified, such as disorganized parking areas and street vendors, as well as a lack of universal design facilities for people with disabilities. Practical Implication: These findings can serve as a reference for the Jambi Provincial Government, particularly the Department of Public Works and Spatial Planning, to transform the GOS management system from a reactive to a preventive-collaborative approach by involving community participation to ensure the sustainability of the park's social and ecological functions. Originality: This study contributes to the literature on green open space management by highlighting public response as an evaluation indicator, particularly in the context of urban parks in Jambi City, which remains underexplored.